THE DIRECT EFFECT OF THE CONSTITUTION AND THE APPLICATION OF LEGAL NORMS IN THE CONTEXT OF THE SUPREMACY OF THE CONSTITUTION (PART 1) - Sargsyan, Nora (State and Law, 2021)
THE DIRECT EFFECT OF THE CONSTITUTION AND THE APPLICATION OF LEGAL NORMS IN THE CONTEXT OF THE SUPREMACY OF THE CONSTITUTION (PART 1)The Constitution of the Republic of Armenia both in the version of 1995 (Article 6, part 2), as well as in the version of 2005 (Article 6, part 1) provided that the Constitution had a supreme legal force and its norms apply directly. At the same time, the Constitution in the version of 2005 stipulated that the state was restricted by the fundamental human rights as the directly applicable law (Article 3, part 3). Article 5 of the Constitution in the version of 2015 has eliminated the general provision on the direct effect of the whole Constitution (part 1), maintaining it only with respect to fundamental rights and freedoms (Article 3, part 3).This article analyzes the origin of the concept of "direct effect" of the Constitution, its essence and the need for its pronouncement in the constitution (I). Then the essence and necessity of the constitutional declaration of direct effect of fundamental rights is explained (II). Afterwards, the practical question whether the hierarchy of legal norms is the same as the hierarchy of their application is discussed (III).
Keywords: Constitution, fundamental rights, direct effect, hierarchy of application of legal norms, supremacy of the Constitution, supreme legal force, constitutional control.